2003
DOI: 10.1152/ajpcell.00289.2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of K-Cl cotransporter activity on activation of volume-sensitive Cl channels in human osteoblasts

Abstract: The whole cell recording mode of the patch-clamp technique was used to study the effect of hypotonic NaCl or isotonic high-KCl solution on membrane currents in a human osteoblast-like cell line, C1. Both hypotonic NaCl or isotonic high-KCl solution activated Cl- channels expressed in these cells as described previously. The reversal potential of the induced Cl- current is more negative when activated through hypotonic NaCl solution (-47 +/- 5 mV; n = 6) compared with activation through isotonic high-KCl soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…More recently, this same group suggested that volume-sensitive chloride channel is involved in KCl-induced chloride conductance in human osteoblasts, which is activated by volume increases induced by K ϩ and Cl Ϫ influx through K-Cl co-transporter (22). In the present study, we also observed high KCl-induced chloride conductance in PC12 cells.…”
Section: Kcl-induced Rac1 Activation and Moesin Phosphorylation Are Dsupporting
confidence: 85%
See 3 more Smart Citations
“…More recently, this same group suggested that volume-sensitive chloride channel is involved in KCl-induced chloride conductance in human osteoblasts, which is activated by volume increases induced by K ϩ and Cl Ϫ influx through K-Cl co-transporter (22). In the present study, we also observed high KCl-induced chloride conductance in PC12 cells.…”
Section: Kcl-induced Rac1 Activation and Moesin Phosphorylation Are Dsupporting
confidence: 85%
“…DISCUSSION This study demonstrates that 60 mM KCl induces the phosphorylation of moesin at Thr-558 in PC12 cells PKA and Rac1 dependently. To our surprise, this signaling pathway was activated not by the depolarization-induced Ca 2ϩ influx, but rather by K ϩ -induced chloride conductance, which was only recently reported and has not been implicated in the activation of intracellular signaling pathways (16,22). It is well known that KCl induces depolarization of the plasma membrane and Ca 2ϩ influx into PC12 cells and subsequently activates diverse calcium-dependent signaling pathways, such as Ras-ERK.…”
Section: Kcl-induced Rac1 Activation and Moesin Phosphorylation Are Dmentioning
confidence: 80%
See 2 more Smart Citations
“…Like epithelial cells, they exhibit polarised secretory properties. Osteoblasts express at least three families of Cl -channels, including Na + -Cl -cotransporters, potassium (K)-Cl -cotransporters and Na [18]. Activation of the osteoblast can be achieved through cotransporter functions.…”
mentioning
confidence: 99%